THE ROLE OF STIMULUS IN INCREASING TOURIST VISITS - Arvitriani, Erlita; Wahyono, Wahyono (Management Analysis Journal, 2019)
The purpose of this research is to examine the direct and indirect influence of city branding, word of mouth, and perceived value and visiting decisions through visiting interests. The population in this study is visitors of Kampoeng Wisata Batik Kauman Pekalongan. This research used incidental sampling and purposive sampling technique with 115 respondents. Data collection method is used questionnaire method and documentation method. Data analysis of this research is used path analysis, variables is used include city branding, word of mouth, perceived value, visiting interests, and visiting decisions. The results of this research showed that city branding and word of mouth directly did not have a significant influence on visiting decisions. Perceived value and visiting interests have positive and significant influence on visiting decisions. In addition, visiting interests variable able to mediate the effect of city branding, word of mouth, perceived value on visiting decisions.